Analisis Perhitungan Harga Pokok Produksi Menggunakan Metode Full Costing pada Usaha Telangtea - Rossa Amelia Imelda; Anisa Sains Kharisma; Dumadi , Dumadi; Hilda Kumala Wulandari (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the calculation of production costs using the full costing method as the basis for determining the cost of goods manufactured in the TelangTea business. The full costing method calculates all costs associated with the production process, both fixed and variable costs. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of the full costing method produces a higher HPP value than the previous calculation, with a difference of Rp1,725 ​​per cup. Therefore, this method can be a reference for MSMEs such as TelangTea in determining a more appropriate selling price strategy in order to maintain the sustainability and competitiveness of the business.